DIFTONGISASI DALAM BAHASA RIBUN - Dedy Ari Asfar (Balai Bahasa Kalimantan Barat, 2017)
Ribun or Hibun language spoken around the District of TayanHulu, TayanHilir, Bonti, Kembayan, and Parindu, West Kalimantan. This paper discusses the diphthongization in Ribun language. This paper uses phonetic analysis (Collins, 1983, 2016). The result of this paper there are unique diphthongizationin Ribun. Firstly, diphthongization appear to indicate diphthongs with vowels of glide, namely high vowel /u/ and a middle vowel /o/ which followed by of glide at the end of a word, which is not followed by a consonant. Second, the high front vowel /i/, high back vowel /u/, low central vowel /a/, front middle vowel /e/, and the rear middle vowel /o/ experienced of glidein the final syllable position covered consonants. However, the style of thisdiphthongization is different, in this position, high vowel /i/ show of glide [ə] fronts /ʔ/, /h/, and nasal /ŋ/. High back vowel /u/ show of glide [a] front /h/ and of glide [ə] front /h/ and /ŋ/.